RADIKALISME DI MEDIA SOSIAL: PENYEBUTAN DAN KONTEKS SOSIAL PENGGUNAANNYA - Wahid, Abdul; Destitry, Nia Ashton; Rakhmawati, Fariza Yuniar (Jurnal InterAct, 2020)
Radicalism is often only placed face to face between radical groups versus the state. In fact, radicalism is not only born because of the contradiction between the two but involves the mediation of ideas through social media. This paper seeks how the discourse of radicalism on social media by content analysis method on social media during August-September 2018. This study reveals that radicalism on social media is not only related to religious issues. Some of the other issues attributed to radicalism are about elections, politics, government, criminality, and other social issues. The various contexts of the radicalism talks often do not refer to major events, but radicalism is associated with other contexts unrelated to the main event as a reference. This shows how social media is becoming an intermediary for biased "radicalism" discourse.